Risk Factor Analysis of Caesarean Section - Nur Inayah Bakri; Azizah Nurdin; Rosdianah Rahim; Rini Fitriani; Fatmawati Fatmawati (Jurnal EduHealth, 2026)
Background: Maternal mortality rate (MMR) is the number of maternal deaths caused by pregnancy, childbirth, and postpartum or their management. In 2015, the global maternal mortality rate was estimated to reach 303,000 cases. According to WHO (2015), maternal deaths are estimated to be more than 585,000 per year due to pregnancy and/or childbirth. Caesarean section (CS) delivery is a surgical process aimed at delivering a fetus through an incision in the abdominal wall and uterine wall. CS delivery is carried out based on medical indications from both the mother and fetus, which can endanger the lives of both the mother and fetus. The purpose of this study was to determine the risk factors for Caesarean section procedures at the Sitti Khadijah 1 Muhammadiyah Makassar Maternity and Child Hospital (RSIA). Method: The study used a quantitative study with an analytical observational research design with a cross-sectional approach. Results: The results of this study are that maternal age greatly influences pregnancy, a good age for pregnancy ranges from 20-35 years. At that age, the female reproductive organs have developed and functioned optimally. On the other hand, for women aged <20 years or >35 years, it is not good to get pregnant because pregnancy at this age has a high risk, such as miscarriage or failed labor, delivery with assistive devices such as forceps or CS, and can even cause death. Conclusion: Maternal age is a risk factor for cesarean section at Sitti Khadijah 1 Muhammadiyah Makassar Hospital in 2021. Maternal parity is not a risk factor for cesarean section at Sitti Khadijah 1 Muhammadiyah Makassar Hospital in 2021.